Absence of medication-related jaw osteonecrosis after treatment with strontium ranelate in ovariectomized rats - Leomar Emanuel de Almeida MECCA; Amanda Regina FISCHBORN; Jessica Daniela ANDREIS; Gabrielle DELFRATE; Tayline MROCZEK; Natália Mariane RIGO; Fábio Brasil de OLIVEIRA; Myrella Lessio CASTRO; Mario TABA JUNIOR; Marcela CLAUDINO; Gilson Cesar Nobre FRANCO (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study aimed to evaluate the potential of strontium ranelate (SR) in medication-related jaw osteonecrosis (MRONJ) after tooth extraction in ovariectomized rats. Thirty ovariectomized rats were divided into three groups (n = 10): bisphophonate (BP) group (zoledronic acid; 0.4 mg/kg/week), SR group (625 mg/kg/day), and control group (saline solution). The lower first molars were extracted after 60 days of drug therapy. Drug administration was continued for another 30 days after tooth extraction. The mandibles were subjected to clinical, histological, radiographic, and microtomographic evaluations. Only the BP group showed clinical changes, characterized by the presence of 70% (n = 7) and 20% (n = 2) of ulcers and extraoral fistulas. Radiographic evaluation demonstrated bone sequestration only in the BP group (n = 7, 70%). Microtomographic analysis revealed increased bone porosity after ovariectomy, particularly in the the control group (p < 0.05). The BP group showed a higher bone surface density, bone volume, and trabecular number than SR and control groups, but with less trabecular separation (p < 0.05). All the animals in the BP group demonstrated histological osteonecrosis. There was no evidence of osteonecrosis in the control and SR groups, which was characterized by the absence of empty osteocyte gaps and associated with the gradual healing of the extraction area. Also, an increased number of blood vessels and a reduced number of osteoclasts were observed in the SR group (p < 0.05). Therefore, SR treatment increased angiogenesis and osteoclastogenesis in the healing socket and was not associated with MRONJ development after tooth extraction in ovariectomized rats.